VD_FINDINFO AP / 2009 / 74 vom 10. Juni 2009 - VD Tribunal cantonal (2009)
POUVOIR D'EXAMEN, CONSTATATION DES FAITS, COURTAGE, TACITE, FARDEAU DE LA PREUVE, SILENCE | 8 CC, 1 al. 2 CO, 1 CO, 412 CO, 452 al. 1ter CPC